Peran Emotional Attachment dalam Memediasi Faktor-Faktor Penentu Revisit Intention yang Dipengaruhi oleh Tourist Experience - Khairunnisa Sayyidah; Yadi Ernawadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the role of emotional attachment in mediating the influence of tourist experience on revisit intention of tourists at Pangandaran Beach using the Theory of Planned Behavior (TPB) framework, which includes attitude toward behavior, subjective norm, and perceived behavioral control. The research method used was a quantitative survey approach. Data were collected through an online questionnaire from 130 respondents who had visited Pangandaran Beach. Data were then analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of SmartPLS software version 3.0. The results showed that tourist experience had a positive and significant effect on attitude toward behavior and subjective norm. Furthermore, attitude toward behavior, subjective norm, and perceived behavioral control were proven to have a significant effect on emotional attachment and revisit intention. Furthermore, emotional attachment also had a positive and significant effect on revisit intention, thus acting as a mediating variable in the relationship between TPB factors and revisit intention. The conclusion of this study is that a positive tourist experience can shape attitudes, social norms, and perceived control in tourists, which in turn strengthen emotional attachment and encourage tourists' intention to revisit Pangandaran Beach. Keywords : Tourist Experience, Emotional Attachment, Theory Of Planned Behavior